PENGELOLAAN FASILITAS DI KAWASAN AGROWISATA RUMBAI KOTA PEKANBARU - Dwi Ramadhani; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The agro-tourism village is a village that was originally named Rumbai Bukit Village, the name Rumbai Bukit was changed due to the expansion that occurred in the city of Pekanbaru in 2016, then Rumbai Bukit changed its name to Agrotourism Village. This name was established to create an area that becomes an agro-tourism area or a plantation area that educates about plantation issues. The management of this agrotourism area is managed by farmer groups in this agro-tourism village. According to researchers, the tassel agro-tourism area will become an agro-tourism object or plantation tourism because it has the same criteria as the understanding of agro-tourism itself, because the tassel agro-tourism area has a large enough land to become a tourist attraction at the level of plantations or farms that are educated, but the development is itself has its problems. The obstacles that occur are the lack of human resources to manage the land itself and the lack of support from the government. Keywords: management, facilities, tourism objects, agro-tourism.